Reversible reaction kinetic of tetraester formation simulation from secondary data: effect of temperature / Fatin Nabila Mohd Aripin - Mohd Aripin, Fatin Nabila (2019)
Polyol ester synthesized from palm oil methyl ester (POME) are environmentally friendly, biodegradable and non-toxic bio-lubricants. A kinetic model that describe chemical transesterification of palm oil-based methyl esters (POMEs) with pentaerythritol (PE) has been developed. The reaction is believed to be a series reaction whereby POME and PE reacted to form an intermediates of PE monoester, PE diester, PE triester and a designed product of PE tetraester. However, the data that were key in in the Matlab is based on overall reversible transesterification reaction. The model considers the transesterification reaction to take place in both forward and reverse directions. The resulting kinetic equations were solved using ode45 solver function in MATLAB. The obtained results were comparing the simulated curve with experimental data. From the results, a good reaction rate was observed only for temperature up to 170℃. The kinetic reaction rate equation used able to predict the value of rate constant with accurate as temperature increase up to 170℃ while temperature at 180℃ indicated at higher temperature tends to reverse the reaction.